An industry involvement to enhance the HCI small-scale project learning experience - Kamaruddin, Azrina; Abdullah, Salfarina; Mohd Norowi, Noris; Admodisastro, Novia Indriaty; Mansor, Evi Indriasari (Science Publishing Corporation, 2018)
Human-computer interaction (HCI) is one of the courses that require in-depth involvement with the end-user to build usable and useful software. The course consists of both theory and practical aspects. One element in this course is doing project work. Throughout the semester, the project has been about a lecturer assigning groups of students with project topics for them to complete by the end of the semester. It is a common practice and has led the students to stagnant learning experience throughout the semester. In order to make students’ learning experience more challenging and engaging, the project has included the industry as part of its 14 weeks duration. The industry was involved in giving the project title, persona, and conducted formative and summative assessments. Finally, an interview session was conducted with the students to obtain information about their learning experiences with the industry involvement while doing their project. The study received both positive and negative feedback from students about this approach.